Evaluation of Real-Time RT-PCR Assay for Routine Laboratory Diagnosis of Classical Rabies in Post-Mortem Brain Samples from Naturally Infected Different Species of Animals - Gurcay, Metin; Parmaksiz, Ayse; Kilic, Ayse (Kafkas Univ, Veteriner Fakultesi Dergisi, 2014)
In this study; the real-time RT-PCR assay was evaluated for laboratory diagnosis of classical rabies in post mortem brain samples from naturally infected different animals species. The material consisted of 75 suspected brain samples brought from 11 different provinces, belonging Eastern and Southeastern Anatolia region, including Elazig, Malatya, Diyarbakir, Mardin, Sirnak, Batman, Tunceli, Mus, Bingol, Hakkari and Bitlis in year of 2011. These samples were from 36 dogs (33 normal, 3 autolytic), 13 cattle, 6 sheep, 6 donkeys, 4 horses, foxes, 3 wolves, 2 cats, and one goat. The samples were autolytic in 3 of 75 (4%), whereas 72 (96%) of 75 samples were freshly arrived to the laboratory. Due to badly autolysis of 3 samples, they could not be examined by fluorescent antibody test (FAT) and mouse inoculation test method (MIT). Seventy two of 75 samples were tested with both fluorescent antibody test (FAT) and mouse inoculation test method (MIT), whereas all the samples (75 of 75) were examined by optimizing real-time RT-PCR assay in which the primary for classical rabies virus and TaqMan prob set were used. Fresh brain homogenates from Cornu ammonis in carnivores and Cerebellum in herbivores were used for FAT and MIT. As a result, 51 of 72 samples were positive with FAT, 52 of 72 samples with MIT, whereas 52 of 72 were positive in real-time RT-PCR. In fresh brain samples, with MIT results in mouse brain, real time RT-PCR test results showed complete relation each other. As both fluorescent antibody test (FAT) and mouse inoculation test method (MIT) could not be applied to the autolytic samples, the real time RT-PCR assay was the only choice. Consequently, real-time RT-PCR assay could be utilized in autolytic samples conveniently as well as confirmatory to FAT in in vitro conditions.
Do?al olarak enfekte olmuş farkli{dotless} tür hayvanlardan, post-mortem olarak elde edilen beyin numunelerinde, klasik kuduzun rutin laboratuvar teşhisinde real time RT-PCR testinin de?erlendirilmesi
Keywords: Rabies Diagnosis; Classical Rabies Virus; Real-Time RT-PCR